2017
DOI: 10.3892/ol.2017.7404
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate genes that may contribute to the metastasis of prostate cancer by bioinformatics analysis

Abstract: Abstract. To screen for marker genes associated with to the metastasis of prostate cancer (PCa), in silico analysis of the Gene Expression Omnibus dataset GSE27616, which included 4 metastatic and 5 localized PCa tissue samples, was performed. Differentially expressed genes (DEGs) were identified. Their potential functions were identified by Gene Ontology and Kyoto Encyclopedia of Gene Genomes pathway enrichment analyses. Furthermore, protein-protein interaction (PPI) networks for DEGs were constructed using C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…The results showed that a total of 2,000 DEGs were identified in PCa compared to normal group, including 1,000 upregulated and 1,000 downregulated genes respectively. Previous studies have demonstrated that co-expression genes were frequently involved in similar biological function and signal pathway ( 2 , 9 ). Therefore, GO analysis and KEGG pathway analysis was further performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that a total of 2,000 DEGs were identified in PCa compared to normal group, including 1,000 upregulated and 1,000 downregulated genes respectively. Previous studies have demonstrated that co-expression genes were frequently involved in similar biological function and signal pathway ( 2 , 9 ). Therefore, GO analysis and KEGG pathway analysis was further performed.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer (PCa) is one of the most common malignancies in men globally and the second leading cause of cancer associated mortality in developed countries ( 1 , 2 ). Like other cancers, PCa is considered to be a disease which caused by age, diet and gene aberrations ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the putative drug targets for metastasis have no known function or enzymatic activity and in silico analysis often finds these genes categorized into seemingly unrelated pathways such as lipid metabolism or vesicular transport [94][95][96][97].…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, CCL4 can contribute to the metastasis to the bone by binding to CC chemokine receptor type 5 (Sasaki, Baba et al 2016). The genes in the "regulation of T cell activation" category, HLA-DR or CD4, also play a critical role in the metastasis in the metastasis of melanoma (Costantini and Barbieri 2017), breast cancer (DeNardo, Barreto et al 2009), and prostate cancer (Liu, Guo et al 2018).…”
Section: Discussionmentioning
confidence: 99%